The role of reference frames in memory recollection. (2019) - Riva, Giuseppe; Di Lernia, Daniele; Serino, Andrea; Serino, Silvia
Abstract: In this commentary on Bastin et al., we suggest that spatial context plays a critical role in the encoding and retrieval of events. Specifically, the translation process between the viewpoint-independent content of a memory and the viewpoint-dependent stimuli activating the retrieval (mental frame syncing) plays a critical role in spatial memory recollection. This perspective also provides an explanatory model for pathological disturbances such as Alzheimer's disease.